Mutation in NRAS in familial Noonan syndrome – case report and review of the literature. Issue 1 (December 2015) - Ekvall, Sara; Wilbe, Maria; Dahlgren, Jovanna; Legius, Eric; van Haeringen, Arie; Westphal, Otto; Annerén, Göran; Bondeson, Marie-Louise
Abstract Background Noonan syndrome (NS), a heterogeneous developmental disorder associated with variable clinical expression including short stature, congenital heart defect, unusual pectus deformity and typical facial features, is caused by activating mutations in genes involved in the RAS-MAPK signaling pathway. Case presentation Here, we present a clinical and molecular characterization of a small family with Noonan syndrome. Comprehensive mutation analysis ofNF1, PTPN11, SOS1, CBL, BRAF, RAF1, SHOC2, MAP2K2, MAP2K1, SPRED1, NRAS, HRAS andKRAS was performed using targeted next-generation sequencing. The result revealed a recurrent mutation inNRAS, c.179G > A (p.G60E), in the index patient. This mutation was inherited from the index patient's father, who also showed signs of NS. Conclusions We describe clinical features in this family and review the literature for genotype-phenotype correlations for NS patients with mutations inNRAS . Neither of affected individuals in this family presented with juvenile myelomonocytic leukemia (JMML), which together with previously published results suggest that the risk for NS individuals with a germlineNRAS mutation developing JMML is not different from the proportion seen in other NS cases. Interestingly, 50 % of NS individuals with anNRAS mutation (including our family) present with lentigines and/or Café-au-lait spots. This demonstrates a predisposition to hyperpigmented lesions inNRAS- positive NS individuals. In addition, the affected father in our family presented with a hearing deficit since birth, which together with lentigines are two characteristics of NS with multiple lentigines (previously LEOPARD syndrome), supporting the difficulties in diagnosing individuals with RASopathies correctly. The clinical and genetic heterogeneity observed in RASopathies is a challenge for genetic testing. However, next-generation sequencing technology, which allows screening of a large number of genes simultaneously, will facilitate an early and accurate diagnosis of patients with RASopathies.